2014
DOI: 10.1063/1.4871403
|View full text |Cite
|
Sign up to set email alerts
|

Ti2MnZ (Z=Al, Ga, In) compounds: Nearly spin gapless semiconductors

Abstract: Ti2MnZ (Z=Al, Ga, In) compounds with CuHg2Ti-type structure are predicted to have the different width of band gap in two spin channels and exhibit a nearly spin gapless semiconductivity. There are different origins of the band gap in spin-up and spin-down channels. The width of the band gap can be adjusted by changing the lattice parameter or doping congeners. These compounds are completely-compensated ferrimagnets with a zero magnetic moment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 18 publications
5
26
0
Order By: Relevance
“…The SGS character of Ti 2 MnAl was also confirmed by Jia et al 42 Wollman et al 43 confirmed the conclusion of Meinert et al that direct exchange interactions are responsible for the magnetic order in Mn 2 CoAl studying a wide range of Mn 2 -based Heusler compounds and predicted a Curie temperature of 740 K using the spherical approximation. 44 Skaftouros et al have discussed in detail the behavior of the total magnetic moment in inverse Heusler compounds including the SGS materials.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The SGS character of Ti 2 MnAl was also confirmed by Jia et al 42 Wollman et al 43 confirmed the conclusion of Meinert et al that direct exchange interactions are responsible for the magnetic order in Mn 2 CoAl studying a wide range of Mn 2 -based Heusler compounds and predicted a Curie temperature of 740 K using the spherical approximation. 44 Skaftouros et al have discussed in detail the behavior of the total magnetic moment in inverse Heusler compounds including the SGS materials.…”
supporting
confidence: 72%
“…Finally, we should shortly discuss the values of the atomic spin magnetic moments presented in Table I 42. Since in each study a different full-potential ab-initio method has been used, we can be confident of the validity of our results.…”
Section: A Spin Gapless Semiconducting Behavior and Magnetic Momentsmentioning
confidence: 99%
“…2,12 A specific aim of SGS research is to develop materials having compensated ferrimagnetic or antiferromagnetic spin structures, such as half-metallic antiferromagnets (HMAFMs). 3,12,13 Compared to ferromagnetic SGSs, these materials exhibit either small or no net magnetization, which is favorable due to the absence of magnetic stray fields, which could otherwise cause interference between neighboring elements in nanoelectronic devices.…”
mentioning
confidence: 99%
“…Recently, an interesting new class of materials, namely, spin-gapless semiconductors, has attracted much attention due to potential applications in spintronics. [1][2][3][4][5][6] These materials are characterized by a zero band gap in one spin channel and by a finite band gap in the other channel, and therefore are different from ferromagnetic materials with semiconducting electron transport, including dilute magnetic semiconductors, which have long been investigated for semiconductor spintronics. 7,8 Spin-gapless semiconductors (SGS) are attractive because they combine advantages of half-metallic (HM) magnets and zero-gap semiconductors.…”
mentioning
confidence: 99%
“…The compounds with this peculiar transport property are known as spin gapless semiconductors because exhibit a semiconducting character in one spin channel and zero band gap in the other. Theoretical description of electronic structures and ground-state magnetism of several spin gapless semiconductors were provided via Density Functional Theory (DFT) [27]. Some compounds like Mn 2 CoAl, have been grown as bulk samples or synthesized as thin films [28,29].…”
Section: Introductionmentioning
confidence: 99%